Axiological Study Towards the Law Number 18/2019 about Pesantren - Muh. Luthfi Hakim; A. Habiburrohman Aksa (The Institute of Research and Service Community IPMAFA Pati, 2021)
This study aims to analyze the law of pesantren axiologically as well as the response of the top academic pro-counter that appears on the birth of pesantren’s law. This research is normative legal research that is the object of study focused on law No. 18/2019 about pesantren. The approach that the authors used is the conceptual approach, this approach aims to find the intent and purpose of such legislation. The data collection method is done by using the method of documentation or library materials, then the data is analyzed by how to describe and perform the axiological analysis. The results of this study are: First, in the axiological study, the birth of pesantren’s law provided many benefits in the form of recognition of equality for students who graduated from pesantren, in recognition of diversity about learning model in pesantren, the governance of independent pesantren as well as recognition of diversity about models and learning methods in pesantren. Second, the emergence of pesantren can provide many benefits for pesantren institution, then the charges which consider that pesantren’s law is government intervention towards the pesantren cannot be justified.